Propuesta para la optimización de procesos productivos para la faenadora de aves de corral "pollos de campo". - Casa Casa, Brayan Raul (2023)
The objective of this research project carried out at the poultry slaughterhouse "Polls del Campo" was to improve production times by optimizing the production process at the poultry slaughterhouse "Polls del Campo". Once the information on the problem was defined, we proceeded to compile the referential academic foundations of the production processes to have a clearer approach to the improvement of the production processes, which allowed the study, analysis, and execution of the basic activities of the proposal of this work. Through the application of quantitative research based on the use of time and movements and the identification of 3 bottlenecks, the situational diagnosis was presented, and the way in which the solution of the established research problem allowed for improving the productivity of the business with its respective diagrams. After analyzing the business situation, an aerial conveyor belt was implemented which optimized the production times, obtaining very favorable results, with a total time of 715 min with an efficiency of 94.08% in the slaughtering line, noticing an improvement in the production processes in comparison with the old times which were 980 min, with an efficiency of 76.56%.